2020
DOI: 10.1016/j.nicl.2019.102130
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity markers of depression in advanced Parkinson's disease

Abstract: HighlightsPatient-specific 42-ICNs template was created from 156 PD patients’ rs-fMRI data.6 FC markers significantly contributed to depression discrimination in PD.Classifiers achieved the mean accuracy of 82.4% for depression diagnosis in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…A RSFC study in DPD found the increased ALFF in the DMN compared with the NDPD and HCs. Other previous studies also found that the BGN, DMN, LFPN, and SN were involved DPD (Hu, Song, Li, et al., 2015), which facilitated the advancement of more detailed and integrative neural models of DPD (Lin et al., 2019; Wei et al., 2017).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A RSFC study in DPD found the increased ALFF in the DMN compared with the NDPD and HCs. Other previous studies also found that the BGN, DMN, LFPN, and SN were involved DPD (Hu, Song, Li, et al., 2015), which facilitated the advancement of more detailed and integrative neural models of DPD (Lin et al., 2019; Wei et al., 2017).…”
Section: Discussionmentioning
confidence: 79%
“…A previous study on FC markers of depression in advanced PD also found RSFC features located in the subcortical, auditory, SMN, VIN, cognitive control, DMN, and cerebellar networks. These networks were significantly relevant to classification and provided preliminary evidence that can characterize DPD patients compared with NDPD (Lin et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety and depression are prominent non-motor symptoms of Parkinson’s disease (PD) that are clinically debilitating ( Seppi et al, 2019 ) and may predate the onset of motor signs ( Postuma et al, 2015 ). Functional imaging studies in patients with PD and comorbid anxiety ( Dan et al, 2017 ; Wang et al, 2017 ) and depression ( Luo et al, 2014 ; Dan et al, 2017 ; Wang et al, 2018 , 2020 ; Lin et al, 2020 ) point to involvement of prefrontal cortical areas, but the associated circuit mechanisms are poorly understood. Much progress has been made in understanding circuit mechanisms related to motor signs of PD utilizing invasive intracranial recording at both cortical ( Panov et al, 2017 ) and subcortical ( Brittain and Brown, 2014 ) sites in the motor network.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, rodent studies using systematic activity mapping after acute and chronic stress have been useful to understand functional consequences of stress-related pathology. For example, functional magnetic resonance imaging (fMRI) studies in CRS mice identified dendritic remodeling of the PFC, HPC, and amygdala with altered functional connectivity across regions of the default mode network 39 , in which activity changes are linked to symptom emergence in MDD 40 , PTSD 41 , Parkinson's disease 42 , and substance abuse disorders 43 . Immediate early gene (IEG) markers, such as c-Fos, similarly yield high spatiotemporal resolution for characterizing functional alterations induced by chronic stress.…”
Section: Introductionmentioning
confidence: 99%